PENGENALAN LANGKAH AWAL BERINVESTASI DALAM PASAR MODAL DI ERA MILENIAL - Nuha, Sukma Uli; Cahyadi, Nur; Purnomo, Syefri Wirayudha (Universitas Muhammadiyah Gresik, 2023)
The introduction of the capital market for Accounting Study Program Students, Faculty of Economics and Business, Muhammadiyah University of Gresik aims to educate students to be literate in capital market investment so that they are expected to be interested in participating in capital market investment literacy education and are interested in investing by opening a capital market account. The implementation method was carried out in several stages starting from the participant data collection stage, coordination with the Accounting Student Association, IDX-UMG Investment Gallery and Phintraco Sekuritas. The result of the service activity is an increase in knowledge and further understanding regarding literacy and how to invest through stocks. In addition, all participants in this activity have been able and succeeded in opening a share account directly.